Women's Boarding School: Forms of Gender Justice for Female Santri - Sofiana, Naela; Afad, Mochammad Najmul; Farah, Nada Alfa; Fajariyah, Nur; Hamid, Nur (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2023)
This research explores women's pesantren as a forum for Islamic religious education for women to learn Islam and other soft skills that will be needed in the future. The location of this research is Nurul Huda Islamic Boarding School, Pandansari Batang Regency. Qualitative research methods, in-depth interview data collection techniques, and participatory observation of this research were conducted. The results of this research show that it is Pesantren Nurul Huda, a traditional Islamic boarding school or pesantren whose students live together under the guidance of a Pak Kyai and Bu Nyai. Pak Kyai and Bu Nyai guide their students to become good female leaders by adhering to the teachings of Islam because Islam does not prohibit women from being leaders in society. Women's boarding schools empower women to create gender equality between men and women, but that does not mean women have to be equal to men. Women's empowerment prioritises women's independence so that they are not too dependent on men.